DIGITAL TRANSFORMATION OF BANKING STRUCTURES AS A TOOL FOR IMPLEMENTING THE ANTI-CRISIS INVESTMENT POLICY OF UKRAINE - Kozhyna, Alla; Diachenko, Svitlana; Zubchyk, Oleh; Tkachenko, Ihor (Public Management and Policy, 2026)
The article examines the digital transformation of Ukraine’s banking structures as a strategic tool for implementing anti-crisis investment policy for 2021–2025. Under the legal regime of martial law and macroeconomic instability, the mobilization of internal and external resources is of great importance for Ukraine’s economic stability, necessitating the need to increase the effectiveness of this state policy and the relevance of the study. It has been proven that, under conditions of existential challenges posed by full-scale armed aggression and macroeconomic instability, the digitalization of the financial sector has transformed from a technological trend into a basic institutional mechanism for ensuring stability and investment activity. The purpose of the article is to theoretically substantiate and develop conceptual principles for using the digital transformation of the banking system as a public management mechanism for implementing the state’s anti-crisis investment strategy. The study uses a combination of general scientific and specialized methods: a systems approach to analyze the interaction among financial market entities; institutional analysis to examine the regulatory and legal support for digitalization; a comparative method to compare domestic experience with practices in EU countries (Estonia, Poland, Lithuania). It was determined that the integration of digital banking services, artificial intelligence and Open Banking technologies forms a new architecture of state investment policy. The institutional capacity of state bodies to regulate the digital financial space was analyzed. The scientific novelty of the research results lies in the development of the author’s conceptual model of interaction “state – digital bank – investor”, which is based on the implementation of digital standards, ensuring cyber resilience and the use of innovative tools (digital military bonds, e-hryvnia). In the context of practical significance, specific recommendations were formulated for state authorities and the National Bank of Ukraine to harmonize the regulatory environment with EU norms (PSD2, eIDAS, DORA) and to strengthen the protection of critical information infrastructure.